1661. The association of spirometric impairment and history of TB: a population based study in Uganda. (31st December 2020) - Robertson, Nicole M; Porterfield, J Zachary; Kayongo, Alex; Kirenga, Bruce; Kalyesubula, Robert; Checkley, William; Thornton, Alice; Siddharthan, Trishul
Abstract: Background: Pulmonary tuberculosis (TB) is the leading infectious cause of death globally with an estimated 1.7 billion people currently infected with Mycobacterium tuberculosis and at risk of developing TB. While the treatment of drug-susceptible pulmonary TB is highly effective, up to 50% of TB survivors have varying degrees of residual pathological and functional conditions potentially leading to chronic sequelae. Post-TB patients have reported respiratory symptoms, reduced quality of life, and increased risk of mortality. The objectives of this study are to describe the prevalence and lung function in individuals with post-TB exposure status in Uganda. Methods: We performed a secondary data analysis of the Lung Function in Nakaseke and Kampala (LiNK) study, which is a population-based cohort in urban and rural settings in Uganda. Trained fieldworkers randomly selected homes and administered standard questionnaires to adults 35 years or older that were full-time residents of each setting. Prior TB diagnosis and treatment was self-reported by participants. Results: Among the study population (N = 1559), 50 participants (3.2%) self-reported successfully treated TB. Among this subset of participants 21 (42.0%) were HIV positive, 9 (18.0%) were ever smokers, 6 (12.0%) were current smokers, and no participants had a prior COPD diagnosis. Mean (SD) age and body-mass index (BMI) at enrollment was 48.5 (SD 10.7) years and 22.2 (SD 3.9) kg/m2 respectively. The mean ± SD pre-bronchodilator FEV1/FVC was 72.9% (12.1%) for patients with successfully treated TB and 79.6% (0.08%) (p< 0.0001) for those without prior TB. Within these groups, 30% of patients with successfully treated TB and 9% of patients without prior TB had an FEV1/FVC suggestive of possible COPD. Comparison of FEV1/FVC Conclusion: We found a high burden of residual effects of pulmonary TB on lung function and development of COPD, potentially increasing the global burden of COPD. Screening for chronic respiratory diseases following successful TB treatment is needed to improve lung function. Further research is needed to study lung function and quality of life in TB survivors in LMICs, where the burden of pulmonary TB is highest. Disclosures: All Authors : No reported disclosures